2020
DOI: 10.1177/1071100720937645
|View full text |Cite
|
Sign up to set email alerts
|

Pes Planus Deformity and Its Association With Hallux Valgus Recurrence Following Scarf Osteotomy

Abstract: Background: Hallux valgus recurrence is an unsatisfactory complication, with many causes postulated. This study investigated the effect of pes planus on recurrence after scarf osteotomy. Methods: A total of 183 feet were retrospectively reviewed. All patients were treated with a scarf osteotomy and if required Akin osteotomy. We measured preoperative lateral talus first metatarsal angle (T1MA) to study pes planus; an angle of under −4 degrees was considered pes planus. We measured pre and postoperative hallux … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 44 publications
(101 reference statements)
0
41
0
Order By: Relevance
“…42 Since its formal introduction in the 19th century, hallux valgus (HV) deformity has been one of the most commonly investigated and treated pathologies of the foot owing to its high prevalence and symptomatic nature. 12,27,32,38,41,44,50,52,54,78,96 Although HV has received a considerable amount of scientific attention over the last century, its pathogenesis is still not entirely understood. 23,63…”
Section: Introductionmentioning
confidence: 99%
“…42 Since its formal introduction in the 19th century, hallux valgus (HV) deformity has been one of the most commonly investigated and treated pathologies of the foot owing to its high prevalence and symptomatic nature. 12,27,32,38,41,44,50,52,54,78,96 Although HV has received a considerable amount of scientific attention over the last century, its pathogenesis is still not entirely understood. 23,63…”
Section: Introductionmentioning
confidence: 99%
“…2 That pathology is complex and not fully understood when considered in the context of a concomitant pes planus deformity. 1,3,5 The surgical technique used was as per the previously published descriptions from your unit. 4,6 Our standard practice is to make a Z osteotomy by producing a longitudinal axial cut starting 5 mm from the dorsal surface of the metatarsal head and moving proximally to the inferior flare of the metatarsal shaft.…”
Section: Dear Editormentioning
confidence: 99%
“…That pathology is complex and not fully understood when considered in the context of a concomitant pes planus deformity. 1,3,5…”
mentioning
confidence: 99%
“…We read with great interest recent publication of the article by Heyes et al 3 The authors investigated the effect of pes planus on recurrence after scarf osteotomy and concluded that the prevalence of hallux valgus recurrence correlated with the severity of flatfoot.…”
mentioning
confidence: 99%
“…Although we are impressed, there are some concerns regarding their study. First, Heyes et al 3 measured the preoperative lateral talus first metatarsal angle (T1MA) and divided their cohort into 3 groups depending on the severity of the pes planus (normal, mild, and severe). They did not measure postoperative T1MA.…”
mentioning
confidence: 99%